The Peoples' Sermon : Preaching as a Ministry of the Whole Congreagation - Hannan, Shauna K. (Book collections on Project MUSE., 2021)
In The Peoples' Sermon, Shauna K. Hannan argues that preaching is not a solo endeavor. It is a communal practice, a ministry of the whole congregation that is most faithful when the process is shared. She invites readers to reflect on what preaching is and to explore roles in the congregation's preaching ministry. Further, she guides readers and their communities through a process that will equip hearers for their roles in the preaching ministry.